Comparing the benefits of Cognitive Stimulation Therapy with an adapted collaborative version on traditional outcomes, loneliness, and socioemotional skills: a pilot study - Domenicucci, Riccardo; Carbone, Elena; Sella, Enrico; Belacchi, Carmen; Sarlo, Michela; Borella, Erika (Frontiers in Psychology, 2025)
BackgroundCognitive Stimulation Therapy (CST) is among the psychosocial interventions with strongest evidence of efficacy for the treatment of dementia. It has been argued that people with dementia (PwD) can also benefit from collaboration and teamwork with peers. The aim of this pilot study was to evaluate the benefits of a new Collaborative CST (C-CST) protocol, vis-à-vis the Standard CST (S-CST), on traditional and underexplored, psychosocial and socioemotional outcomes.MethodsIn this single-blind randomized controlled trial, we enrolled a convenience sample of 28 PwD (mean age = 87 ± 5.74 years) from six Italian residential facilities and randomly allocated them to either S-CST or C-CST. We examined the benefits in traditional outcomes (i.e., global cognitive functioning, mood, and psychological and behavioral symptoms), as well as in overlooked psychosocial outcomes (i.e., social and emotional loneliness) and socioemotional skills [i.e., cognitive and affective theory of mind (ToM) and definitional competence of emotions].ResultsResults indicated that both C-CST and S-CST maintained PwD mood but that only S-CST supported global cognitive functioning and mitigated psychological and behavioral symptoms at postintervention. Both CST protocols also reduced social loneliness (but not emotional loneliness) and ameliorated the definitional competence of emotions at postintervention, with C-CST showing larger effect sizes compared to S-CST. Only S-CST fostered cognitive ToM (but not the affective one) at postintervention.ConclusionDifferent CST protocols provided nuanced benefits across traditional, psychosocial, and socioemotional outcomes. S-CST remains the only protocol capable of promoting benefits in cognition and key dementia-related symptoms, whereas the new C-CST has emerged as a promising and easily implementable protocol with the potential to alleviate loneliness and support some socioemotional skills in PwD.